STUDY ON EVALUATION OF SFLT1/PLGF RATIO FOR PREDICTION OF PRE-ECLAMPSIA IN THE SECOND AND THIRD TRIMESTER OF PREGNANCY: AN OBSERVATIONAL STUDY. - Jha, Richa (Student's Journal of Health Research Africa, 2024)
Background Pre-eclampsia (PE) is a critical pregnancy complication leading to adverse perinatal outcomes like fetal growth restriction, stillbirth, oligohydramnios, eclampsia, and HELLP syndrome. An imbalance between pro-angiogenic (PlGF) and anti-angiogenic (sFLT-1) factors increases the sFLT-1/PlGF (sFlt1/PlGF) ratio, detectable about four weeks before the symptoms appear. The study was conducted to determine the predictive value of the sFlt1/PlGF ratio for the development of PE in high-risk pregnant women during the late 2nd and 3rd trimesters. Methods The study included 50 high-risk pregnant females between 24 and 32 weeks of gestation. Participants were selected based on criteria such as age > 30 years, BMI > 30 kg/m², previous history of PE, PAPPA < 0.4 MoM, increased UtA PI at 11-13 weeks, twin pregnancy, IVF conception, and history of FGR. The sFlt1/PlGF ratio was determined, and participants were monitored for the development of Pre-Eclampsia. The study determined the specificity, sensitivity, positive predictive value (PPV), and negative predictive value (NPV). Results Among the participants, 70% were over 30 years of age, and 30% were under 30. The sFlt1/PlGF ratio demonstrated a high NPV of 96.7%, indicating a reliable prediction for the absence of PE within a week. The PPV was 63.5%, suggesting a strong indication of PE development with a high ratio (>38). The sensitivity of the ratio was 92.3%, and the specificity was 81.08%, confirming its effectiveness in correctly identifying both the presence and absence of pre-eclampsia. Conclusion The sFlt1/PlGF ratio is a valuable predictive tool for identifying the possibility of the development of PE in high-risk pregnancies, with high NPV, sensitivity, and specificity. It effectively aids in early identification and management, potentially improving maternal and fetal outcomes. Recommendations Clinicians should consider incorporating the sFlt1/PlGF ratio in the routine assessment of high-risk pregnant women to enhance early detection and intervention strategies for pre-eclampsia.